O idei uniwersytetu katolickiego = On the essence of the catholic university - Magier, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The present article examines the essence (idea) of the Catholic university, focusing on key assertions and categories that define this concept. The paper is based on selected source literature and adheres to the principles of the analytical research model. The structure of the article includes: definitional issues, observations on the historical development of Catholic universities, and considerations regarding contemporary aspects of their functioning. The author identifies three main categories that collectively encapsulate the idea of the Catholic university: the reconciliation of science with Revelation, the moral aspects of scientific research, and personalism.
Keywords: uniwersytet; uniwersyte katolicki; wiara; nauka; prawda; moralność; personalizm; university; catholic University; faith; science; truth; morality; personalism